2006
DOI: 10.1158/0008-5472.can-05-3020
|View full text |Cite
|
Sign up to set email alerts
|

De novoInduction of a Cancer/Testis Antigen by 5-Aza-2′-Deoxycytidine Augments Adoptive Immunotherapy in a Murine Tumor Model

Abstract: Recent studies suggest that immunotherapy targeting specific tumor-associated antigens (TAAs) may be beneficial in cancer patients. However, most of these TAAs are tumor type specific and heterogeneous among patients, thus limiting their applications. Here, we describe the de novo induction of a cancer/testis antigen (CTA) for immunotherapy of tumors of various histologies. The murine CTA P1A, normally expressed only in a few tumor lines, could be induced de novo in all P1A-negative cancer lines of eight histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 54 publications
3
113
1
Order By: Relevance
“…30,31 The integrity of RNA and random primers-synthesized cDNA was confirmed by the amplification of all cDNA samples with mouse b-actin-specific primers, as previously described. 6 Five mL of each RT-PCR sample were run on Quantitative Methylation-Specific PCR analyses Bisulfite conversion was carried out on 500 ng genomic DNA using EZ DNA Methylation-Gold TM Kit (Zymo Research, cat # D5005), according to the manufacturer's protocol.…”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…30,31 The integrity of RNA and random primers-synthesized cDNA was confirmed by the amplification of all cDNA samples with mouse b-actin-specific primers, as previously described. 6 Five mL of each RT-PCR sample were run on Quantitative Methylation-Specific PCR analyses Bisulfite conversion was carried out on 500 ng genomic DNA using EZ DNA Methylation-Gold TM Kit (Zymo Research, cat # D5005), according to the manufacturer's protocol.…”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…The medical importance of CG-X antigens is supported by the observation that vaccine-induced CD8 þ T-cell responses to CG-X antigens, but not to melanoma differentiation antigens, correlates with tumor-free and overall survival in melanoma patients (Reynolds et al, 2003). Treatment with agents that increase the expression of CG-X antigens, including DAC (Karpf et al, 2004;Sigalotti et al, 2004) and zebularine (Cheng et al, 2004), constitute an intriguing therapeutic approach by which antitumor immunity to CG-X antigen-directed vaccines could be improved (Karpf and Jones, 2002;Maio et al, 2003;Guo et al, 2006). However, the toxicity and pleiotropic effects associated with nucleoside analog DNMT inhibitors could be a barrier to the successful clinical implementation of this combination strategy (Karpf and Jones, 2002).…”
Section: Ac-k9mentioning
confidence: 99%
“…4 With regard to transplantation, recent studies have suggested that hypomethylating agents may potentiate GVL effects. [5][6][7][8] Therefore, a pilot study of azacytidine treatment after discontinuation of immunosuppressants was performed in MDS patients who relapsed after transplantation.…”
mentioning
confidence: 99%